Commercial fisheries in a mega unregulated floodplain river: Assessment of the most favourable hydrological conditions for its preservation. Issue 1 (15th November 2019) - Rabuffetti, Ana Pia; Espínola, Luis A.; Abrial, Elie; Amsler, Mario L.; Blettler, Martin C. M.; Eurich, Maria F.; Eberle, Eliana G.
Abstract: This paper deals with the hydrological variability effects on the primary commercial fish species inhabiting the main channel and the floodplain of the large Paraná River in its middle reaches in Argentina. Analysing more than eight decades (1935–2016) of information on the most frequent and abundant commercial species in conjunction with hydrological levels and temperature, our results show that spring–summer floods of a certain magnitude ( c . 6 m) and durations (> 80 days) are crucial for sustaining commercial fisheries. Moreover, the frequency of these floods was modulated by the decadal climatic fluctuations that have occurred over the past 100 years in the Paraná Basin. An insight into the probable incidence of some anthropogenic influences is also provided.